The impact of Work from Home on Employee Productivity in the private Banking sector - Hewawasan, H.H.P.D.; Weerasoory, W.A.H. P.; Piyarathne, K.M.C.H.; Ekanayaka, R.M.K.S.; Jayasuriya, N.A.; Dayapathirana, N. N. (Faculty of Management Studies and Commerce University of Sri Jayewardenepura, 2024)
The COVID-19 pandemic has taken a significant toll on Sri Lanka's private banking sector, including domestically. This study investigates the impact of working from home on staff productivity in this area. The banking system in Sri Lanka has changed over time from traditional money-lending institutions to sophisticated financial institutions that finance financial growth and wealth management. Employee productivity (EP), driven through technological innovation and operational change, has been a key motif in the trajectory of the banking enterprise. The reason for this observation is to analyze the impact of work-from-home (WFH) on EP in the private banking sector of Sri Lanka. Look at the impact of using quantitative strategies that include regression analysis between key variables WFH, EP, and job satisfaction. WFH can affect your work-life balance (WLB). This was done during the Covid-19 pandemic and its findings may not be generalizable to other settings. This is because of the verification of findings and awareness of the massive and negative effects of working from home on EP. These relationships are assessed using reports from a wide range of sources including the Central Bank of Sri Lanka, industry guidelines, and clinical literature. By considering the specific issues and opportunities within the Sri Lankan banking sector, this investigation contributes to our knowledge of how local influences EP in a private banking context. The findings of this study supply points that can be used to improve regulations and techniques to optimize EP while adapting to the changing painting environment in the public non-banking quarter of Sri Lanka.
Keywords: Banking system, WFH, Employee productivity, Job satisfaction